Age-stratified risk analysis of gastric cancer: a retrospective hospital-based study of helicobacter pylori, smoking, and dietary patterns in South China across three age groups - Liu, Yantong; Zhang, Dongdong; Lin, Rubing; Lian, Yifan; Zhang, Wei (Frontiers in Oncology, 2026)
BackgroundGastric cancer (GC) remains a leading cause of cancer mortality globally, with a multifactorial etiology involving infectious, behavioral, and dietary risk factors. However, age-specific variations in these factors are not well understood.MethodsWe conducted a hospital-based retrospective study of 903 pathologically confirmed GC cases recruited from several tertiary medical centers in south China. Participants were stratified into three age groups (≤30, 31–55, and >55 years). Key variables—including Helicobacter pylori infection, smoking, obesity, dietary habits, and medical history—were analyzed using chi-square tests and multivariable logistic regression to assess age-related differences in risk factor prevalence and associations.ResultsThe prevalence of H. pylori infection and smoking significantly increased with age (p < 0.05), and both factors are known contributors to gastric cancer risk in prior studies. Smoked/grilled food consumption showed a significant association with GC, particularly among older adults (OR = 2.05, 95% CI: 1.29–3.27, p = 0.002). Obesity and low fruit/vegetable intake were not statistically significant. Socioeconomic indicators, including urban employee basic medical insurance (UEBMI) coverage, also exhibited age-related patterns but showed mixed associations with GC risk.ConclusionThis study highlights age-specific disparities in GC risk profiles and underscores the cumulative exposure patterns of H. pylori infection, smoking, and dietary carcinogens. However, given the retrospective and hospital-based design, causal relationships cannot be established, and selection bias may exist. Despite these limitations, the findings provide an epidemiological basis for age-tailored prevention strategies, emphasizing early eradication of H. pylori, smoking cessation, and dietary interventions for high-risk populations.